Impact of regenerative agricultural practices on forage maize (Zea mays L.) yield under semiarid conditions - Tofiño-Rivera, Rodrigo; Piraneque-Gambasica, Nelson Virgilio; Aguirre-Forero, Sonia Eperanza (Revista de Ciencias Agrícolas, 2026)
Forage production is crucial for livestock in dry tropical regions due to its adaptability and nutrient supply, especially during the dry season when pastures deteriorate. A field experiment was conducted under dry Caribbean conditions in Cesar, Colombia, during 2023 to evaluate the regenerative production system of forage maize (Zea mays L.) ‘AGROSAVIA V-117’, planted at a density of 100,000 plants/ha. The experiment was laid out with five treatments: Control Fertilization (FNC), FNC + Amendment, FNC + Biofertilizers, FNC + Amendment + Biofertilizers, FNC + Amendment + Biofertilizers + Cover, FNC + 20%. Results showed green forage production ranging from 79.92 to 92.89 t/ha for FNC+biofertilizer and FNC+20%, respectively. The traditional fertilization + amendment + biofertilizer + cover crop achieved the highest values of ear production (20.64 t/ha). As for forage dry mass accumulation, the 20% improved conventional fertilization had the highest value with 25.48 t/ha, followed by conventional fertilization + biofertilizer with 24.86 t/ha. Although no significant statistical differences were observed between treatments, the results exceeded the national averages, highlighting the potential for incorporating regenerative, economically viable, and environmentally sustainable practices into livestock production systems in semiarid conditions.